The neurobiology of childhood trauma—aldosterone and blood pressure changes in a community sample. (14th September 2022) - Terock, Jan; Hannemann, Anke; Klinger-König, Johanna; Janowitz, Deborah; Grabe, Hans J.; Murck, Harald
Abstract: Objective: Childhood trauma is an important risk factor for the onset and course of psychiatric disorders and particularly major depression. Recently, the renin-angiotensin-aldosterone system, one of the core stress hormone systems, has been demonstrated to be modified by childhood trauma. Methods: Childhood trauma was obtained using the Childhood Trauma Questionnaire (CTQ) in a community-dwelling sample ( N  = 2038). Plasma concentrations of renin and aldosterone were measured in subjects with childhood trauma (CT; N  = 385) vs. subjects without this experience (NoCT; N  = 1653). Multivariable linear regression models were calculated to assess the associations between CTQ, systolic and diastolic blood pressure, renin and aldosterone concentrations, and the ratio of aldosterone and systolic blood pressure (A/SBP). Results: CT subjects demonstrated higher plasma aldosterone (A) concentrations, a lower systolic and diastolic blood pressure, and a higher A/SBP. In addition, both aldosterone concentrations, as well as A/SBP, correlated with the severity of childhood trauma. These findings could not be attributed to differences in concomitant medication. Conclusions: In conclusion, childhood trauma was associated with neurobiological markers, which may impact the risk for psychiatric disorders, primarily major depression. The altered A/SBP ratio points to a desensitisation of peripheral mineralocorticoid receptor function, which may be a target for therapeutic interventions.